The implementation of debate technique to improve students’ speaking skill.” ( A classroom action research at grade nine of Oxford Center)= Nghiên cứu về việc áp dụng các thủ thuật tranh luận để thúc đẩy khả năng nói của học sinh (Một nghiên cứu hành động - Trần, Thị Hảo (University of Languages and International Studies, 2017)
There is no doubt that speaking skill is one of the essential skills in teaching and learning English. Nowadays, a lot of students have difficulty in learning speaking skill. From this fact, the thesis was conducted to evaluatewhetherthe activity called “debate technique”could help the student improve their speaking level. The material that the researcher chose was “Solutions –Intermediate Student’s book”. This book is in current use for the grade nine at Oxford center. The data collection instruments employed in this study were tests (pre-test and post-test), questionnaire for students and questionnaire for teachers. These tests helped researcher to find out how far the implementation could help students improve their speaking skill. In addition,the questionnaires helped the author find out the effective ways that debate technique should be conducted. Research findings haveindicated that after applying debate technique, the students’ speaking score increased significantly. Based on the findings, the suggestions would be given for better application of the use of debate technique in speaking lessons